Women, workplace protest and political identity in England, 1968-85 - Moss, Jonathan (Manchester University Press, 2019)
This book draws upon original research into women's workplace protest to deliver a new account of working-class women's political identity and participation in post-war England. Focusing on the voices and experiences of women who fought for equal pay, skill recognition and the right to work between 1968 and 1985, it explores why working-class women engaged in such action when they did, and it analyses the impact of workplace protest on women's political identity. A combination of oral history and written sources are used to illuminate how everyday experiences of gender and class antagonism shaped working-class women's political identity and participation. The book contributes a fresh understanding of the relationship between feminism, workplace activism and trade unionism during the years 1968-1985
Keywords: Geschichte 1968-1985; Politische Identität; Arbeitskampf; Arbeitnehmerin; England; Working class women / Political activity / Great Britain / History / 20th century; Women in the labor movement / Great Britain / History / 20th century; Women in the labor movement; Working class women / Political activity; Great Britain; 1900-1999; History